Educational Needs During COVID-19: MOOCs Experiences Among Global Family Physicians - Özden Gökdemir; Halime Seda Küçükerdem; Sudip Bhattacharya; Maria Bakola; Mohammed Idris Shariff (Gazi Medical Journal)
Objective: Family physicians (FPs) worldwide have rallied to minimize the indirect effects of the disease. FPs are always on the frontline, “first in- last out”, and took the lead in fighting the virus-caused disease in the acute phase of the coronavirus disease-2019 (COVID-19) epidemic. They played a vital role in examining, informing, and monitoring patients in primary care health centers, as well as in centers set up specifically for COVID-19. However, due to poor knowledge of COVID-19, which changes rapidly, FPs had to update their practical and theoretical knowledge about this novel coronavirus on a daily. Massive open online courses (MOOCs) are courses that use an online application and can reach the entire world. In this study, we aimed to determine the opinions and suggestions of FPs in meeting their educational needs related to COVID-19 through MOOCs and to create solutions. Methods: The study was planned to be held with FPs who completed MOOCs training and completed the questionnaire. Due to international participation, the survey was conducted in English. Ethical approval was obtained from the Ethics Committee of İzmir University of Economics. Participation was entirely voluntary. Results: Our study revealed that as the age of FPs increases, their confidence in their ability to treat patients also increases. FPs showed a positive attitude toward MOOCs as sources of continuous medical education and group activity (p<0.005). For the qualitative part of the study, three themes were significant: “i) opinions about concerns about changes of primary care, ii) views and attitudes about the information need and access to information, iii) attitudes and beliefs about MOOCs”. Conclusion: By completion of this course, FPs broadened their knowledge about COVID-19 management. This gave them capacity to save and improve the lives of countless patients infected by the novel coronavirus worldwide. Sharing their experiences with COVID-19 could be a way to cope with stress.